Civil szervezetek szerepe a területi foglalkoztatási megállapodásokban - Rubaj, Anita (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
In present study I would like to demonstrate the role of civil organizations in the territorial employment pacts of the South Transdanubian region. In changing number and to various ex-tent, but civil organizations take a part in all employment pacts of the region. The collaboration and the participation in the elaboration of the local employment development ideas are impor-tant, because they are in a daily contact with the target groups of the pact. The results of my study show that the civil organizations participating in the pacts are diverse and unique. To exploit the opportunity arising from these characteristics, civil organizations should cooperate in the planning and execution of their programs. The resulting synergy effect can significantly contribute to the achievement of both individual civil organizations’ and pacts’ goals.